Combination of resolvin E1 and lipoxin A4 promotes the resolution of pulpitis by inhibiting NF‐κB activation through upregulating sirtuin 7 in dental pulp fibroblasts. Issue 5 (11th April 2022) - Liu, Xiaochen; Wang, Chunmeng; Pang, Liping; Pan, Liangliang; Zhang, Qi
Abstract: Objectives: To determine whether the combination of resolvin E1 (RvE1) and lipoxin A4 (LXA4) could promote resolution of pulpitis and to investigate the mechanism. Materials and Methods: Preliminary screening was first conducted in four specialized pro‐resolving mediators (SPMs). Real‐time quantitative polymerase chain reaction, western blotting, enzyme‐linked immunosorbent assay and double‐immunofluorescence labelling were employed to assess the expression of RelA, SIRT1, SIRT6, SIRT7 and pro‐inflammatory factors. Dental pulp fibroblasts (DPFs) were transfected with siRNA to assess the biological role of SIRT7. A pulpitis model was utilized to evaluate the in vivo curative effect. Results: Preliminary results showed that RvE1 and LXA4 reduced the expression of RelA more markedly than other two SPMs. Both RvE1 and LXA4 treatment downregulated nuclear factor kappa B (NF‐κB) activation and increased the expression of SIRT1, SIRT6 and SIRT7, more so in combination than alone. Double‐immunofluorescence labelling showed that SIRT7 co‐localized with p‐p65 and Ac‐p65 in the nucleus. Inhibiting ChemR23 and ALX reversed the expression of RelA mRNA, p‐p65 and Ac‐p65 proteins, pro‐inflammatory factors, SIRT1, SIRT6 and SIRT7. Silencing SIRT7 significantly increased p‐p65 and Ac‐p65 protein levels and decreased SIRT1 and SIRT6 expression. In vivo experiments showed that combined administration of RvE1 and LXA4 promoted pulpitis markedly to resolution. Conclusions: Combination of RvE1 and LXA4 effectively inhibited NF‐κB activation by upregulating SIRT7 expression in DPFs, leading to reduced production of pro‐inflammatory factors and promotion of pulpitis resolution. Abstract : Combination of resolvin E1 and lipoxin A4 could effectively upregulate the expression of SIRT7, inhibiting nuclear factor kappa B activation by dephosphorylation and deacetylation in dental pulp fibroblasts, and promote pulpitis resolution. Meanwhile, silencing SIRT7 may affect the expression of SIRT1 and SIRT6, indicating that they may synergistically promote inflammation resolution.